Multi-Level Process Integration of Heat Pumps in Meat Processing - Klinac E; Carson JK; Hoang D; Chen Q; Cleland DJ; Walmsley TG (MDPI (Basel, Switzerland), 2023)
Many countries across the globe are facing the challenge of replacing coal and natural gas-derived process heat with low-emission alternatives. In countries such as New Zealand, which have access to renewably generated electricity, industrial heat pumps offer great potential to reduce sitewide industrial carbon emissions. In this paper, a new Pinch-based Total Site Heat Integration (TSHI) method is proposed and used to explore and identify multi-level heat pump integration options at a meat processing site in New Zealand. This novel method improves upon standard methods that are currently used in industry and successfully identifies heat pump opportunities that might otherwise be missed by said standard methods. The results of the novel method application suggest that a Mechanical Vapour Recompression (MVR) system in the Rendering plant and a centralized air-source heat pump around the hot water ring main could reduce site emissions by over 50%. Future research will develop these preliminary results into a dynamic emissions reduction plan for the site, the novel methods for which will be transferrable to similar industrial sites.
Keywords: heat pump; total site analysis; energy saving; industrial heat integration; decarbonization; meat processing